Glucocorticoids and cardiovascular disease - Walker, Brian R (European journal of endocrinology, 2007)
Chronic excessive activation of glucocorticoid receptors induces obesity, insulin resistance, glucose intolerance, dyslipidaemia and hypertension. Subtle abnormalities of the hypothalamic-pituitary-adrenal axis and/or of tissue sensitivity to glucocorticoids are also associated with these cardiovascular risk factors in patients with the metabolic syndrome. Furthermore, glucocorticoids have direct effects on the heart and blood vessels, mediated by both glucocorticoid and mineralocorticoid receptors and modified by local metabolism of glucocorticoids by the 11beta-hydroxysteroid dehydrogenase enzymes. These effects influence vascular function, atherogenesis and vascular remodelling following intra-vascular injury or ischaemia. This article reviews the systemic and cardiovascular effects of glucocorticoids, and the evidence that glucocorticoids not only promote the incidence and progression of atherogenesis but also modify the recovery from occlusive vascular events and intravascular injury. The conclusion is that manipulation of glucocorticoid action within metabolic and cardiovascular tissues may provide novel therapeutic avenues to combat cardiovascular disease.